Bentuk-bentuk Pelanggaran Tindak Pidana Pemilu oleh Penyelenggara pada Pemilihan Anggota DPRD Kota Medan 2024-2029 - Laksono, Agung Dwi; Kusbianto, Kusbianto; Sitompul, Ariman (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the legal regulations, forms of violations, and enforcement mechanisms of electoral criminal offenses committed by election organizers during the election of members of the Medan City Regional House of Representatives for the 2024–2029 period. The research employs a normative legal method with statutory, conceptual, and case-based approaches. The findings indicate that the legal framework for electoral crimes is comprehensively regulated under Law Number 7 of 2017 concerning General Elections, which stipulates criminal sanctions such as imprisonment, fines, and administrative penalties for election officials proven to have committed violations. The types of violations identified include manipulation of voter lists, abuse of authority, vote buying, and vote inflation or reduction. The enforcement mechanism involves several key institutions including the Election Supervisory Body (Bawaslu), the Integrated Law Enforcement Center (Gakkumdu), the police, the public prosecutor’s office, and the Election Organizer Honorary Council (DKPP), all of which are mandated to act independently, transparently, and professionally. Legal enforcement in this context serves not only as a repressive tool to punish violations but also as a preventive measure by promoting legal awareness and strengthening the integrity and accountability of election organizers. Therefore, firm and consistent law enforcement is a crucial prerequisite to ensure elections are conducted fairly, honestly, democratically, and with high integrity, thereby maintaining public trust in the electoral process.